Ameliorated Impact of Fenugreek Seed Extract on Some Blood Cellular and Biochemical Parameters in Female Albino Rats Exposed to Lead Acetate - Abduljalil Naser, Rozhya; Yousif Mameik, Rabar; Shareef Mahmood, Nazar M.; Bapir Chato, Kurdo (Kurdistan Journal of Applied Research, 2020)
Lead acetate (LA) is considered as the common hazardous compund present in our habitat. It has a several diverse-organ toxicant effect in various healthy issues included diseases of the hepatic, renal, and other body systems. Fenugreek seeds (Trigonella foenum graecum L.) were used in curing medicine and as food supplement since ancient times. After that, their antioxidant and hepatoprotective properties have been studied. Therefore the presented was based on their biological properties of this plant and conducted to examine the protective impact of fenugreek seed extract upon LA toxicity on some blood cellular and biochemical parameters of female albino rats (Rattus norvegicus). Twenty eight female rats were randomly and equally divided into four groups each one contain seven rats as following; first group received basal diet and tap water ad libitum. Second group received basal diet and LA 80 mg/L with water ad libitum. Third group received basal diet contained 2.5% fenugreek seed extract and LA 80 mg/L with water ad libitum. Fourth group received basal diet contained 2.5% fenugreek seed extract with water ad libitum. Rat’s administration was continued daily for two weeks respectively. The administration of rats with LA produced significant reduction in liver weight, food intake, while it increased triglyceride (TG), alkaline phosphatase (ALP), aspartate aminotransferase (AST), uric acid (UA) and creatinie (CR). While supplemented diet with 2.5% Fenugreek seed extract improved body weight, organ weight, lipid peroxidation, TG, ALP, and AST. Our results plead for the profiteering of fenugreek seeds as a dietary supplement, because it showed protective effect of their content in polyphenolic flavonoids, antioxidant and membrane-protective effects, against exposure to the LA compound to protect injurious risk.